Job Opportunities for Youth Entering the Labor Force: Skill and Training Needs of Employers in the Milwaukee Metro Area - (:unkn) unknown (My University, 2007)
The Employment and Training Institute conducted a survey in May 2006 of employers in the Milwaukee Region for the Private Industry Council of Milwaukee County to determine job openings available for immediate hire. This paper examines current job opportunities for young people entering the labor force in the Milwaukee metro area and identifies fields where targeted training offers opportunities for career building, long-term employment, and family-sustaining jobs.
Keywords: youth employment; teens; skills mismatch; spatial mismatch